The Role of Parental Involvement and Future Orientation in Junior High School Students’ Career Choice - Hadi, Abdul; Danianty, Vina (PPSDP International Journal of Education, 2025)
Nowadays, many adolescents face difficulties in determining the right career path. These challenges stem from various internal and external factors, leading to confusion, uncertainty, and hesitation among students when making decisions about further education or career aspirations. This study aims to examine the influence of parental involvement and future orientation on students’ career decisions. The population of this research comprises all students of SMP Negeri 2 Godean, while the sample consists of eighth-grade students selected through purposive sampling. The study employs multiple linear regression analysis, yielding findings that indicate parental involvement has a significant effect on career choice (t-table 0.023 < 0.05), future orientation significantly influences career selection (t-table 0.00 < 0.05), and both variables simultaneously have a significant impact on career determination (sig. 0.00 < 0.05). These findings underscore the importance of parental roles and the development of a clear future orientation to prevent obstacles in the career decision-making process. Additionally, they highlight the responsibility of school counselors in facilitating parental involvement and fostering students’ future orientation.